Effective classroom management : - Smith, Colin (Routledge, 1993)
This latest new edition of Effective Classroom Management is written for new teachers and those who train and guide them. It combines sound practical advice on lesson organisation and teaching methods with an exploration of teachers' feelings about themselves and the children they teach. In this second edition, classroom management is considered from four aspects: management in the classroom; mediation with individuals; modification of behaviour and monitoring school discipline.